Upregulation of embryonic stem cell marker Nanog in human gingival fibroblasts stimulated with cyclosporine A: An in vitro study - Cheng-Chia Yu; Ni-Yu Su; Chia-Ming Liu; Li-Chiu Yang; Chung-Hung Tsai; Yu-Chao Chang (Elsevier, 2017)
Background/purpose: Gingival overgrowth is a common side effect of medication with the immunosuppressant cyclosporine A (CsA). This study proposed to verify whether Nanog, an embryonic stem cell marker, contributes to gingival overgrowth stimulated with CsA in human gingival fibroblasts (HGFs). Materials and methods: The effect of CsA on HGFs was used to elucidate whether Nanog expression could be induced by CsA using quantitative real-time reverse transcription-polymerase chain reaction and Western blotting. Cell growth in CsA-treated HGFs with Nanog lentivirus-mediated short hairpin RNA interference knockdown was evaluated by tetrazolium bromide reduction assay. Results: CsA upregulated Nanog transcript in HGFs in a dose-dependent manner (P < 0.05). CsA was also shown to increase Nanog protein expression in HGFs in a dose-dependent manner (P < 0.05). In addition, downregulation of Nanog by lentiviral infection significantly inhibited CsA-stimulated cell growth in HGFs (P < 0.05). Conclusion: CsA upregulated Nanog expression and cell growth in HGFs, while silencing Nanog effectively reversed these phenomena. Nanog may act as a major switch in the pathogenesis of CsA-induced gingival overgrowth.